2019
DOI: 10.1186/s12937-019-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer survivors’ preferences for and evaluations of a post-treatment dietary intervention

Abstract: Background Dietary preferences vary depending on cancer type. The purpose of this study was to report dietary intervention preferences and a study program evaluation from post-treatment head and neck cancer survivors participating in a dietary intervention. Methods Between January 2015 and August 2016, 24 head and neck cancer survivors participated in a 12-week randomized clinical dietary intervention trial that promoted weekly consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…No geral, os resultados do presente estudo sugerem que a maioria da amostra considerou que uma intervenção via telefone pode ser eficaz para fazer face a problemas der índole psicológica, sendo provável nela participar. De facto, a investigação já levada a cabo no âmbito das intervenções desta natureza tem evidenciado que as mesmas têm sido aceitáveis junto de sobreviventes de cancro (Crowder et al, 2019;Escriva et al, 2018;Forbes et al, 2019;Salsman et al, 2019;Seiler et al, 2017). Os nossos dados evidenciam que uma maior percentagem de sobreviventes com idade superior a 65 anos percecionou uma maior utilidade deste género de intervenção, comparativamente àqueles das restantes faixas etárias.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No geral, os resultados do presente estudo sugerem que a maioria da amostra considerou que uma intervenção via telefone pode ser eficaz para fazer face a problemas der índole psicológica, sendo provável nela participar. De facto, a investigação já levada a cabo no âmbito das intervenções desta natureza tem evidenciado que as mesmas têm sido aceitáveis junto de sobreviventes de cancro (Crowder et al, 2019;Escriva et al, 2018;Forbes et al, 2019;Salsman et al, 2019;Seiler et al, 2017). Os nossos dados evidenciam que uma maior percentagem de sobreviventes com idade superior a 65 anos percecionou uma maior utilidade deste género de intervenção, comparativamente àqueles das restantes faixas etárias.…”
Section: Discussionunclassified
“…Nos Açores, o número reduzido de equipas especializadas em saúde mental e os constrangimentos impostos pela insularidade no acesso aos serviços de saúde (e.g., distâncias até aos hospitais centrais, carência de transportes, custos envolvidos na deslocação dentro e fora da Região), tornam mais desafiante o desenho e a implementação de intervenções psicológicas que permitam ultrapassar estes constrangimentos. Como forma de responder a alguns dos aspetos acima referidos, os estudos de revisão mais recentes têm vindo a avaliar os efeitos da utilização da tecnologia (e.g., telemedicina, e-health, telefone, apps) na prestação de cuidados de suporte e de follow-up para sobreviventes de cancro (Crowder et al, 2019;Escriva et al, 2018;Forbes et al, 2019). Dadas as especificidades geográficas do arquipélago açoriano (e.g., dispersão geográfica) e, consequentemente, as barreiras geográficas, práticas/estruturais, que podem influenciar a procura de ajuda especializada, o recurso à tecnologia pode ser uma via promissora na prestação de apoio psicológico aos sobreviventes desta Região.…”
Section: A Intervenção Psicológica Para Sobreviventes De Cancrounclassified
“…[ 10 ] With a compromised deglutition functioning, maintaining a nutrition balance is a big challenge in such cases. [ 11 ] A multicentric study reported that pain and scar in the region of surgery may dissuade the patients from consuming food normally. Those with more than 10 kg of weight loss postsurgically were more dependent on mashed food.…”
Section: Discussionmentioning
confidence: 99%
“…Though one study suggested some survivors prefer telephone follow-up, this was limited to dietetic advice rather than monitoring of disease recurrence with HNC clinicians. 25 Boyajian et al suggested a tiered system, whereby a set of core issues were identified (appointment planning, monitoring investigations, information regarding side effects and strategies for fear of recurrence) and once satisfactorily met further issues and needs could be addressed as highlighted by individuals as being of importance. 10 This approach would allow patients to have input into their own priorities once the core aspects of surveillance had been addressed.…”
Section: Additional Themesmentioning
confidence: 99%